Não preferência para alimentação e aspectos biológicos de Spodoptera eridania em cultivares de feijão-caupi - De Souza, Bruno Henrique Sardinha [UNESP]; Boiça Júnior, Arlindo Leal [UNESP]; Da Silva, Anderson Gonçalves [UNESP]; Lobato Rodrigues, Nara Elisa [UNESP] (My University, 2012)
The aim of this paper was to evaluate the no-preference for feeding and biological aspects of Spodoptera eridania fed on cowpea cultivars BR17 Gurgueia, BRS Urubuquara, BRS Nova Era, Sempre Verde, BRS Milênio and BR3 Tracuateua. In free-choice test, leaf discs were placed in Petri dishes where one third instar larvae per cultivar was released, whereas in no-choice test one leaf disc was placed per Petri dish where one caterpillar per cultivar was released, evaluating their attractiveness after 1, 3, 5, 10, 15, 30, 60, 120, 360 and 720 minutes, as well as the leaf area consumed. Randomized blocks and complete randomized blocks design were used for free-choice and no-choice tests, respectively, with six treatments and 10 replications. The evaluation of the biological parameters of S. eridania was carried out in Petri dishes where recently hatched caterpillars were transferred in the proportion of one per dish, and the leafs of the cultivars were offered to them during the whole larval period, and we evaluated: periods and viabilities of larvae and pupae, overall viability, weight of larvae and pupae, sex ratio, longevity and overall cycle. Complete randomized design was used with six treatments and 30 replications. In no- preference for feeding free-choice test the cultivars Sempre Verde and BR17 Gurgueia were the most and the least consumed, respectively. Regarding the effects of cowpea cultivars on larval viability we can infer that BRS Urubuquara and Sempre Verde show antibiosis-type resistance to S. eridania.
No-preference for feeding and biological aspects of Spodoptera eridania on cowpea cultivars
Keywords: Antibiosis; Host plant resistance; Insecta; Vigna unguiculata